TEACHING READING COMPREHENSION BY USING PICTURE STORIES TO THE TENTH GRADE STUDENTS OF SMK SPPN SEMBAWA BANYUASIN - Aswadi Jaya (Jurnal Dosen Universitas PGRI Palembang)
ABSTRAKThe main problem of this reserach was “Is it effective to use picture stories in teaching reading comprehension to The Tenth Grade Students of SMK SPPN Sembawa Banyuasin?” Therefore, the objective of this reserach was to find out whether or not it is effective to teach reading comprehension by using picture stories to The Tenth Grade Students of SMK SPPN Sembawa Banyuasin. The method used in this reserach was the pre-experimental method. The population of this reserach was all of Tenth Grade Students of SMK SPPN Sembawa Banyuasin in the academic year of 2013/2014 with the total number of 134 students. The samples of the reserach were one class taken by using convenience non-random sampling with the total number of 30 students. The data were analyzed by using percentage analysis, conversion of percentage score ranges and the matched t- test. The result of the test showed that teaching reading comprehension by using picture stories to The Tenth Grade Students of SMK SPPN Sembawa Banyuasin is effective. It can be seen from the average score of the students in the pre-test was 48.08. the average score of the students in the post-test was 71.16. the result of t-test calculation was 12.92. From them matched t-test calculation the writer found test t-obtained was 9.779 and the critical value t-table with 0.05 or 5 % significant level with df-1 was 1.697. it show that t-obtained was greater than t-critical value table. It means it was effective to use picture stories in teaching reading comprehension to The Tenth Grade Students of SMK SPPN Sembawa Banyuasin.Keyword: picture stories, reading